Targeting of lactate dehydrogenase C dysregulates the cell cycle and sensitizes breast cancer cells to DNA damage response targeted therapy - Adviti Naik (673163) (2021)
The cancer testis antigen (CTA) lactate dehydrogenase C (LDHC) is a promising anticancer target with tumor‐specific expression and immunogenicity. Interrogation of breast cancer patient cohorts from The Cancer Genome Atlas (TCGA) and Molecular Taxonomy of Breast Cancer International Consortium (METABRIC) indicate that upregulation of LDHC expression correlates with unfavorable prognosis. Although the role of LDHC is well characterized in spermatocytes, its role in tumors remains largely unknown. We investigated whether LDHC is involved in regulating genomic stability and whether it could be targeted to affect tumor cellular fitness. Silencing LDHC in four breast cancer cell lines significantly increased the presence of giant cells, nuclear aberrations, DNA damage, and apoptosis. LDHC‐silenced cells demonstrated aberrant cell cycle progression with differential expression of cell cycle checkpoint and DNA damage response regulators. In addition, LDHC silencing‐induced microtubule destabilization, culminating in increased mitotic catastrophe and reduced long‐term survival. Notably, the clonogenicity of LDHC‐silenced cells was further reduced by treatment with the poly (ADP‐ribose) polymerase (PARP) inhibitor olaparib and with the DNA‐damaging drug cisplatin. This study supports the therapeutic potential of targeting LDHC to mitigate cancer cell survival and improve sensitivity to agents that cause DNA damage or inhibit its repair. Other Information Published in: Molecular Oncology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/1878-0261.13024